A bibliometric and scientific knowledge map study of the drug therapies for asthma-related study from 1982 to 2021 - Zhen, Gao; Yingying, Liu; Weifang, Xu; Jingcheng, Dong (Frontiers in Pharmacology, 2022)
Objective: To produce systematic mapping of how research on drugs for patients with asthma especially severe asthma has evolved over time and identify the evolution of key research themes by using of co-cited references and networks of co-occurring keywords. Methods: A comprehensive search was conducted to analyze all COPD drugs-related articles using WOSCC database from1982 to December 31, 2021. Abstracts and potentially eligible articles, which were retrieved during literature search, were screened by two reviewers. Besides, the CiteSpace (5.8.R1) and VOSviewer (1.6.17) software were utilized to analyze the overall structure of the network, the network clusters, the links between clusters, the key nodes or pivot points, and the pathways. Results: A total of 3234 asthma-drugs related eligible studies were included. USA is the most productive country, Karolinska Inst is the institution with the most asthma drug-related publications. The keywords can be grouped by thematic area, for asthma drug-related studiers, including conventional asthma drugs, monoclonal-antibody, The basis of asthma, pulmonary drug delivery, phenotypes, Two target population, for asthma patients. And for severe asthma drug-related studiers, including monoclonal-antibody, conventional asthma drugs, phenotypes, One target population, The basis of asthma. In 22 major clusters in the co-citation network map of asthma drug-related research, eight different major trends of asthma drug-related research were found, including asthma phenotypes, asthma drugs, types of asthma drugs, establishment of asthma model, traditional medicine, non-drug therapy, promising target in the treatment of asthma and pulmonary delivery. In 30 major clusters in the co-citation network map of severe asthma drug-related research, four different major trends of severe asthma drug-related research were found, including severe asthma phenotypes, types of asthma drugs, asthma model, and monoclonal-antibody. Conclusion: The research hotspots and frontiers are as follows: Fully reveal the potential of existing conventional asthma drugs, determine the best drug delivery, and find the best combination. And from improving patient adherence and the correct use of inhalation devices to ensure the effectiveness of the drug. Continue to explore potential targets for severe asthma or other phenotypes, and develop new targeted drugs to improve asthma control and drug safety.